Technology Integration in the Project Based Learning Model: Bibliometric Analysis 2015-2024 - Ahzari, Serli; Yani, Intan Purnama; Asrizal, Asrizal; Novitra, Fuja (Universitas Negeri Padang, 2024)
This study aims to conduct a bibliometric analysis of scientific publications discussing technology integration in the Project-Based Learning (PjBL) model during the 2015-2024 period. With the evolving 21st-century educational paradigm, PjBL has emerged as one of the most promising pedagogical approaches. In this context, the integration of technology in PjBL becomes an important catalyst that expands the scope and depth of learning experiences while preparing students to face challenges in the digital era. This research applies a bibliometric analysis methodology and systematic literature review, utilizing the Publish or Perish (POP) application for data collection and VOSviewer for data analysis and visualization. The results reveal emerging research trends, collaboration patterns, and focus areas in the scientific literature related to technology integration in PjBL. The bibliometric analysis uncovers research dynamics and knowledge gaps that need to be addressed. These findings provide valuable insights for researchers, practitioners, and policymakers in optimizing the implementation of technology-based PjBL and formulating educational policies responsive to technological developments and 21st-century learning needs. The results of this study are expected to contribute significantly to the academic community and educational practitioners in developing more effective technology-based PjBL implementation strategies and fostering interdisciplinary collaboration to advance education in the digital age.